1993
DOI: 10.1180/minmag.1993.057.386.07
|View full text |Cite
|
Sign up to set email alerts
|

Deformation and metamorphism of massive sulphides at Sulitjelma, Norway

Abstract: The copper-bearing stratabound pyritic massive sulphide bodies contained in metamorphosed basic eruptives of Ordovician age at Sulitjelma in Nordland County, Norway, form one of the important fields of sulphide mineralisation within the Krli Nappe Complex. The sulphide bodies and their enclosing rocks were subject to successive stages of penetrative deformation and recrystallisation during the cycle of metamorphism and tectonic transport caused by the Scandian Orogeny. Textures within the ores and the immediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 42 publications
3
17
0
1
Order By: Relevance
“…This correspondence is almost systematic in Cerro de Maimón and overlaps with the complex deformation history that certainly involved brittle deformation during retrograde metamorphic conditions (e.g. Cook et al, 1993). By means of orientation contrast (OC) imaging and electron backscatter diffraction (EBSD), Barrie et al (2010) concluded that the preservation of annealing textures in greenschist-facies metamorphosed massive sulfides of the Norwegian Caledonides potentially represented surface-driven processes (re-arrangement by a dissolution/syntaxial overgrowth) during metamorphism This conclusion contrasts with the classical assumption that foam textures result from recrystallization (e.g.…”
Section: Accepted M Manuscriptsupporting
confidence: 58%
See 2 more Smart Citations
“…This correspondence is almost systematic in Cerro de Maimón and overlaps with the complex deformation history that certainly involved brittle deformation during retrograde metamorphic conditions (e.g. Cook et al, 1993). By means of orientation contrast (OC) imaging and electron backscatter diffraction (EBSD), Barrie et al (2010) concluded that the preservation of annealing textures in greenschist-facies metamorphosed massive sulfides of the Norwegian Caledonides potentially represented surface-driven processes (re-arrangement by a dissolution/syntaxial overgrowth) during metamorphism This conclusion contrasts with the classical assumption that foam textures result from recrystallization (e.g.…”
Section: Accepted M Manuscriptsupporting
confidence: 58%
“…pyrite alternate with intense microfracturing and blow-apart and porphyroclastic textures, locally developing pressure shadows. Very similar textural relationships and gradations are described in other VMS-bearing districts worldwide that underwent low-grade metamorphism, such as the Iberian Pyrite Belt (Velasco et al, 1998), the Appalachians (Brueckner et al, 2015) or the Norwegian Caledonides (Cook et al, 1993;Barrie et al, 2010;Lockington et al, 2014).…”
Section: Sulfide Formation Deformation Geochemistry and Deriving Cosupporting
confidence: 57%
See 1 more Smart Citation
“…Most of the stratabound massive sulphide deposits in the Norwegian Caledonides were metamorphosed to greenschist or amphibolite facies (Table 2). Pyrrhotite in these deposits has been deformed, recrystallized and annealed during prograde metamorphism ( Table 2 and Vokes, 1968;Cook et al, 1993). Annealing of pyrrhotite is generally thought to be important only above 450~ which is well above 254~ the transformation temperature from mpo to hpo (Fig.…”
Section: Origin Of Lamellar Intergrowthsmentioning
confidence: 98%
“…However, the behaviour of individual sulfide minerals during metamorphism and related deformation of massive sulfide deposits may vary greatly, depending on temperature, strain rate, confining pressure, fluid pressure, differential stress, permeability within the zone of deformation, and the nature of adjacent or matrix-forming sulfides (Ashby and Verrall 1973;Kelly and Clark 1975;Knipe 1989;Cook et al 1993;Duckworth and Rickard 1993). Cox (1987) subdivided deformation mechanisms in sulfide minerals into the following categories: 1) brittle failure and cataclastic flow; 2) low-temperature plasticity (dislocation glide and mechanical twinning); 3) dislocation creep; 4) solution-precipitation creep; 5) solid-state diffusion creep; and 6) grainboundary sliding.…”
mentioning
confidence: 99%